2004
DOI: 10.1007/978-3-540-24693-0_87
|View full text |Cite
|
Sign up to set email alerts
|

Lazy Agent Replication and Asynchronous Consensus for the Fault-Tolerant Mobile Agent System

Abstract: Abstract. In this paper, we propose a low overhead replication scheme for the fault-tolerant mobile agent system. In the proposed lazy replication scheme, execution of a primary agent and migration of its replicas are concurrently processed . Also, the primary agent perforrns asynchronaus consensus with fixed consensus agents so that the consensus step and the replica migration step can concurrently be processed. As a result, the primary agent should not wait for the completion of the replica migration step un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In this study, more than 50% of the experimental studies reported agent size as a performance factor and that the execution time of the agents linearly increases with the increase in size of the agent [14], [40], [41], [42], [36], [46], [7]. In addition, increase in size also lead to replication process having overheads [7], [40].…”
Section: Agent Sizementioning
confidence: 93%
See 4 more Smart Citations
“…In this study, more than 50% of the experimental studies reported agent size as a performance factor and that the execution time of the agents linearly increases with the increase in size of the agent [14], [40], [41], [42], [36], [46], [7]. In addition, increase in size also lead to replication process having overheads [7], [40].…”
Section: Agent Sizementioning
confidence: 93%
“…Transactional Non-transactional Checkpoint [5], [38], [36], [27], [30], [26], [42] [34], [45], [48], [46], [32] Replication [29], [39], [7], [47], [35] [43], [40], [41], [33], [44], [25], [28] Hybrid [14], [31] -------Further analysis shows that both check-pointing and replication-based schemes are used almost equally over the years of consideration (see Figure 6). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations